Fertilization modes and the evolution of sperm characteristics in marine fishes: Paired comparisons of externally and internally fertilizing species. Issue 12 (4th December 2022) - Ito, Takeshi; Morita, Masaya; Okuno, Seiya; Inaba, Kazuo; Shiba, Kogiku; Munehara, Hiroyuki; Koya, Yasunori; Homma, Mitsuo; Awata, Satoshi
Abstract: Fertilization mode may affect sperm characteristics, such as morphology, velocity, and motility. However, there is little information on how fertilization mode affects sperm evolution because several factors (e.g., sperm competition) are intricately intertwined when phylogenetically distant species are compared. Here, we investigated sperm characteristics by comparing seven externally and four internally fertilizing marine fishes from three different groups containing close relatives, considering sperm competition levels. The sperm head was significantly slenderer in internal fertilizers than in external fertilizers, suggesting that a slender head is advantageous for swimming in viscous ovarian fluid or in narrow spaces of the ovary. In addition, sperm motility differed between external and internal fertilizers; sperm of external fertilizers were only motile in seawater, whereas sperm of internal fertilizers were only motile in an isotonic solution. These results suggest that sperm motility was adapted according to fertilization mode. By contrast, total sperm length and sperm velocity were not associated with fertilization mode, perhaps because of the different levels of sperm competition. Relative testis mass (an index of sperm competition level) was positively correlated with sperm velocity and negatively correlated with the ratio of sperm head length to total sperm length. These findings suggest that species with higher levels of sperm competition have faster sperm with longer flagella relative to the head length. These results contradict the previous assumption that the evolution of internal fertilization increases the total sperm length. In addition, copulatory behavior with internal insemination may involve a large genital morphology, but this is not essential in fish, suggesting the existence of various sperm transfer methods. Although the power of our analyses is not strong because of the limited number of species, we propose a new scenario of sperm evolution in which internal fertilization would increase sperm head length, but not total sperm length, and change sperm motility. Abstract : We compared sperm characteristics between seven externally and four internally fertilizing species to investigate the evolutionary effect of fertilization mode, considering sperm competition levels. We found that internal fertilization should increase sperm head length, but not total sperm length, and change sperm motility, whereas sperm competition should affect sperm length and velocity. Our findings provide a new perspective on the evolutionary biology of sperm in fishes.